ACCOUNTING IN COLLEGIATE SCHOOLS OF BUSINESS. - Briggs, L. L. (The Accounting Review, 1930)
Abstract Accounting is recognized as one of the basic tools of quantitative measurement essential to the proper control of business and the accurate analysis of its problems and as such is generally considered to be a fundamental subject in the professional training for business administration. The following study has been made with the purpose of determining what the members of the American Association of Collegiate Schools of Business are doing to further education in accounting. Every collegiate school of business offers a course of elementary accounting which usually takes a year to complete and carries from three to five hours credit per semester. Although the content varies to some extent among the institutions. Very few of the institutions under discussion offer more than one course in auditing. Cost accounting is another standard course in these schools. It is either a one or two semester course with credit ranging from two to six semester hours. Courses in C.P.A. problems or advanced accounting problems are offered by a majority of the members of this association.